What does it take for healthy food retail programmes to be successful? Lessons learned in New York City - Felicia J Setiono; Samantha P Heller; Tashara M Leak (Cambridge University Press, 2024)
Abstract Objective: Healthy food retail programmes (HFRP) in the USA generally aim to increase healthy foods access to improve diet quality and health, yet the impact is mixed. These programmes primarily target adults, even though adolescents frequently and independently visit stores to purchase snacks. This study's aims are to explore successes and challenges of implementing HFRP (Aim 1) and examine how HFRP can be tailored to adolescents (Aim 2). Design: One-time, virtual, semi-structured interviews with individuals who were involved in a HFRP, followed by a socio-demographic characteristics survey. Interviews were designed based on the RE-AIM framework and the Hexagon Tool and analysed using Braun and Clark's (2006) thematic analysis approach. Descriptive statistics were used to summarise participants' socio-demographic characteristics. Setting: New York City (NYC). Participants: Adults (18 years or older) who have designed, implemented and/or evaluated an HFRP in NYC and speak/understand English (n 21). Results: Aim 1: For successes, strategies to build relationships with the community were most discussed. Regarding challenges, securing reliable funding was the hardest to overcome. Suggested solutions included designing profitable HFRP, targeting shortcomings in food distribution systems and increasing consumer demand. Aim 2: Most participants had not considered adolescents in previous HFRP but suggested involving youth in developing HFRP to encourage youth-driven solutions and promote youth advocacy. Conclusions: Future HFRP should focus on activities that help store owners purchase affordable healthy foods from distributors, which translates to affordability for customers. Federal and local policies can assist by funding complementary programmes. Additionally, adolescents should be considered in these efforts.